Genetic variant of ADH1C for predicting survival in esophageal squamous cell cancer patients who underwent postoperative radiotherapy - Xu, Xin; Sun, Zhiyong; Rong, Ling; Wang, Xiaohang; Xu, Lei; Lu, Jun; Ye, Qing; Zhang, Lei; Bai, Yongrui; Ma, Xiumei (Frontiers in Genetics, 2022)
Background: Single nucleotide polymorphisms (SNPs) of essential enzymes for alcohol metabolism ADH1B, ADH1C and ALDH2 is commonly regarded as genetic biomarkers for esophageal squamous cell carcinoma (ESCC) susceptibility. However, there have not been any reports on relations between SNPs of these genes and the prognosis of postoperative radiotherapy in ESCC. The current study aims to understand the associations between gene variants of alcohol metabolism and adjuvant radiotherapy's prognosis in ESCC. Methods: This study retrospectively analyzed 110 ESCC patients from our institution who received adjuvant radiotherapy after the operation. The SNPs of ADH1B rs1229984, ADH1C rs1789924 and ALDH2 rs671 were detected by Sanger sequencing using formalin-fixed paraffin-embedding tumor samples. A nomogram was drawn based on prognostic factors associated with overall survival (OS). Results: ADH1C rs1789924 (C>T) was associated with poor DFS and OS in ESCC patients undergoing adjuvant radiotherapy. Multivariate analysis showed that ADH1C rs1789924 (C>T) was one of the independent prognosis factors of DFS and OS. However, the genotypes of ADH1B SNP rs1229984 and ALDH2 rs671 were not associated with differences in the PFS and OS of these patients. Compared with the AJCC staging system, the nomogram containing the ADH1C genotype can more effectively and accurately predict the survival time of ESCC after surgery and adjuvant radiotherapy. Conclusion: ADH1C rs1789924 might be a prognosis genetic biomarker for ESCC patients undergoing surgery and postoperative radiotherapy.